2014
DOI: 10.3233/asy-141228
|View full text |Cite
|
Sign up to set email alerts
|

Fractal powers in Serrin's swirling vortex solutions

Abstract: We consider a modification of the fluid flow model for a tornado-like swirling vortex developed by Serrin [Phil. Trans. Roy. Soc. London, Series A, Math & Phys. Sci. 271(1214) (1972), 325-360], where velocity decreases as the reciprocal of the distance from the vortex axis. Recent studies, based on radar data of selected severe weather events [Mon. Wea. Rev. 133(9) (2005), 2535-2551; Mon. Wea. Rev. 128(7) (2000), 2135-2164; Mon. Wea. Rev. 133(1) (2005), 97-119], indicate that the angular momentum in a tornado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…These results strongly indicate that established tornadoes exhibit a power-law decay in the tangential velocity and that the magnitude of the exponent correlates with the severity of the tornado. This is consistent with some of the authors' work [17], in which Serrin's "swirling vortex" model [53] is revisited and solutions to the Navier-Stokes and Euler equations are sought for which velocity is proportional to r −α with a general positive α. It is shown that only solutions with 0 < α ≤ 1 are physically reasonable, and that more violent storms would correspond to larger values of α and less violent ones to smaller values of α.…”
Section: Power Laws In the Tangential Velocity Of Tornadoessupporting
confidence: 87%
See 1 more Smart Citation
“…These results strongly indicate that established tornadoes exhibit a power-law decay in the tangential velocity and that the magnitude of the exponent correlates with the severity of the tornado. This is consistent with some of the authors' work [17], in which Serrin's "swirling vortex" model [53] is revisited and solutions to the Navier-Stokes and Euler equations are sought for which velocity is proportional to r −α with a general positive α. It is shown that only solutions with 0 < α ≤ 1 are physically reasonable, and that more violent storms would correspond to larger values of α and less violent ones to smaller values of α.…”
Section: Power Laws In the Tangential Velocity Of Tornadoessupporting
confidence: 87%
“…Self-similarity is also observed in [17], which revisits Serrin's "swirling vortex" model [53] and investigates solutions to the Navier-Stokes and Euler equations in spherical coordinates with the velocity, v, satisfying the power law |v| ∝ r −α , where r is the distance from the vertical coordinate axis and α is not necessarily equal to 1. The streamlines and other physical quantities of the modeled vortices, such as isobars, exhibit self-similarity.…”
Section: Introductionmentioning
confidence: 99%
“…In a related work, Bělík et al (2014) revisit the "swirling vortex" model of Serrin (1972) and investigate solutions to the Navier-Stokes and Euler equation v = r b , where b is not necessarily equal to −1. The streamlines of the modeled vortices exhibit self-similarity, i.e., both the power law and the geometric manifestations of self-similarity are addressed in this work.…”
Section: Self-similaritymentioning
confidence: 99%
“…Nevertheless, Serrin shows that these solutions have rich structures including two-celled vortex. Recently, there has been research on modifying the scaling of the velocity/radial distance dependence in Serrin's vortex solutions, based on radar data observation [4].…”
Section: Introductionmentioning
confidence: 99%